Monetary policy analysis with potentially misspecified models - Marco Del Negro; Frank Schorfheide (Federal Reserve Bank of Atlanta, 2005)
The paper proposes a novel method for conducting policy analysis with potentially misspecified dynamic stochastic general equilibrium (DSGE) models and applies it to a New Keynesian DSGE model along the lines of Christiano, Eichenbaum, and Evans (JPE 2005) and Smets and Wouters (JEEA 2003). We first quantify the degree of model misspecification and then illustrate its implications for the performance of different interest rate feedback rules. We find that many of the prescriptions derived from the DSGE model are robust to model misspecification.
Keywords: 330; Geldpolitik; Unvollkommene Information; Allgemeines Gleichgewicht; VAR-Modell; Modellierung; Schätzung